How Have We Silenced the Everydayness of our Mental Dis-ease, in Mainstream Aotearoa New Zealand? - Player-Bishop, Louise (Auckland University of Technology, 2019)
This study originated with a wondering about my childhood understanding of ‘normal’ and the ‘crazies’ in the mental hospitals down the road. I wondered about the silence between these apparent extremes. Between these two opposites there seemed to be an abyss, a silence that was the ‘normal’. This normal was everywhere but there were no words describing it and no-one appearing to notice it. To understand this silence, this study began with an exploration of the literature on the history of madness in Europe and Aotearoa New Zealand. This created a base for an interpretive hermeneutic analysis. Through this analysis I arrived at three findings: the need for connection; stigma and the process of othering; and the Force. The Force is an intertwining braid that links our past and our traditions to the way we view mental health today. This final finding was key and led to an unexpected turn and personal insight. From this, implications for practice, training and policy were discussed along with strengths and limitations of the study. Gaps and future directions were considered. The conclusion was a reflection that tried to make sense of the findings that were pivotal to this study and especially, the unexpected turn.
Keywords: Madness; Stigma; Psychotherapy; Mental dis-ease; Mainstream; New Zealand; Silence